Understanding Perceptions of Anxiety Disorders and Their Treatment. Issue 2 (February 2016) - Schofield, Casey A.; Dea Moore, Crystal; Hall, Anna; Coles, Meredith E.
Abstract : Abstract: Characterizing areas of limited knowledge about anxiety disorders and their treatment may help inform treatment dissemination efforts and public health programming. In a sample of 626 adults recruited via Amazon's Mechanical Turk, this study evaluated 1) perceptions of symptoms of anxiety disorders and depression, 2) perceived usefulness of coping approaches ( i.e., professional and non-professional help), and 3) awareness of available resources. Results indicated that participants generally recognized that symptoms warranted professional help, and recognition was associated with self-efficacy for seeking mental health care, but not with participants' own symptoms. Furthermore, participants perceived psychotherapy to be the most useful coping approach. Of concern is the perception that symptoms are the result of personal weakness (particularly among male participants and for social anxiety disorder), as well as limited knowledge about publicly available resources. In all, results suggest that there are areas for growth regarding mental health literacy for anxiety disorders.